(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper is concerned with the concepts of upper and lower c-(τ_1,τ_2)-continuous multifunctions. Moreover, several characterizations of upper and lower c-(τ_1,τ_2)-continuous multifunctions are investigated.